Gêneros objetivos e teleologia em Hegel: da natureza à sociedade (Revista Eletrônica Estudos Hegelianos, 2019)
In this article, I explore the metaphysical foundations of Hegel’s social philosophy. Basing myself on an exegetical approach to Hegel’s general metaphysical framework for finite reality which has been popular in the recent literature on Hegel, and which assigns crucial roles to objective kinds (“concepts”) and teleological structures, I examine to what extent Hegel can be seen as applying this framework also to social entities. After summarizing the general exegetical approach in the first three sections, I argue that Hegel sees social reality as ordered by objective, teleologically structured kinds, and use Hegel’s analogy between organism and state to get clearer about the relevant understanding of teleology (or social functions). I argue that Hegel fails to resolve an important problem for his approach, namely the absence of a proper social analogue to biological reproduction and inheritance, and propose a form of social teleological explanation that is apt to fill the resulting gap in Hegel’s theory. I also indicate ideas in Hegel’s approach to social ontology that are of interest independently of Hegel’s normative views on society and politics.